Globalization and taxation: theory and evidence - Priyaranjan Jha; Giray Gozgor (Center for Economic Studies and ifo Institute (CESifo), 2019)
We construct a theoretical model to capture the compensation and efficiency effects of globalization in a set up where the redistributive tax rate is chosen by the median voter. The model predicts that the two alternative modes of globalization- trade liberalization and financial openness- could potentially have different effects on taxation. We then provide some empirical evidence on the relationship between taxation and the alternative modes of globalization using a large cross-country panel data set. On average, globalization is associated with lower taxation but there is some evidence that in countries with high capital-labor ratio, globalization is associated with increased taxation. We make a distinction between de jure and de facto measures of globalization and find a strong negative relationship between taxation and de jure measures of globalization. The results for de facto measures of globalization are mixed.
Keywords: F11; F21; F68; H11; 330; trade liberalization; capital market openness; redistributive taxation; median voter